Evaluating the application of the European spatial development perspective in the United Kingdom: Methodological considerations and emerging trends - Olivier John Sykes (European Regional Science Association (ERSA), 2002)
The aim of this paper is to consider how the emerging European spatial development policy agenda is influencing the performance of regional strategic planning in the United Kingdom. In May 1999 the Ministers of Spatial Planning meeting at Potsdam, Germany, agreed on the final version of the European Spatial Development Perspective (ESDP) to guide spatially significant public policy making at all spatial scales from the Community level, to the regional/local level. The status of the ESDP as a non-binding and indicative, rather than prescriptive, document means that it seeks to guide institutions in the exercise of existing competences, which influence spatial development. Its application is therefore to be achieved through voluntary co-operation based on the principle of subsidiarity. One of the key aims of the ESDP Action Plan agreed at Tampere in October 1999 was the promotion of a spatial dimension in Community and national policies, including the integration of ESDP policy orientations into national spatial planning. Such moves towards a 'Europeanisation of state, regional and urban planning' can be seen as echoing Bruce Milan`s statement in the foreword to Europe 2000 that planning in isolation is no longer possible. Informed by this context, the focus of this paper is the application of the principles of 'Europeanisation' and 'spatialisation' to Regional Planning Guidance (RPG) documents in the UK. The paper will evaluate the extent to which the ESDP and the wider European context for planning are being used to inform and shape the development of RPG for the English regions. National policy on regional planning in England: PPG 11 - Regional Planning (DETR: 2000), makes clear that the European context and the ESDP provide an important context for the preparation of regional plans, and that they should be taken into account when developing the spatial strategy for the region and where appropriate in relation to any relevant policies. Consideration will be given to the way in which the spatial planning policy messages and approach of the ESDP have been integrated into the regional planning process and how they have helped to inform the development of substantive objectives for regional planning policy. The paper is based on work commissioned by the UK Planning Officers Society from the Department of Civic Design at Liverpool University and work completed towards ESRC supported PhD research.
Keywords: 330